Making aid agencies work : reconnecting INGOs with the people they serve - Gibson, Terry (Emerald Publishing Limited, 2019)
The development industry is worth billions. International non-governmental organizations (INGOs) have become an integral component in international development and humanitarian response. Yet as recent scandals at Save the Children and Oxfam have highlighted, such organizations can overstep moral boundaries, raising questions about the scale, power and role of INGOs. Are they dedicated to continuous learning and self-improvement, or are they development dinosaurs driven by their own need for survival and by the political agendas of their paymasters?Drawing upon his experience as an international development practitioner-one who has worked with NGOs large and small, international and local, in over 40 countries-and drawing also upon his own academic research, Terry Gibson addresses these questions head on. He combines large-scale industry analysis with attention to the lives and worlds of the people the aid industry aims to serve, and he demonstrates how to overcome barriers between the two worlds and free flows of learning, resources, and even political influences that might lead to better outcomes.Making Aid Agencies Work is essential reading for practitioners and researchers, as well as for anyone concerned about the future of this vital area of human endeavour.